Análisis estadístico multivariado de variables y eventos relacionados a la inestabilidad de pozo en campo Castilla (2019)
In order to perform a series of guidelines to mitigate or prevent the presence of mechanical well instability events, a multivariate statistical analysis was carried out with the information of variables and instability indicator events to determine the behavior of each variable for each formation. analyzed and what is the most frequent event in these formations. Subsequently, a matrix of selection of both variables and events is carried out, obtaining that the variables with greater relation to instability events are the inclination of the well, the azimuth of the well and the equivalent density of circulation, while the events more critical during drilling are the circulation losses and pipe glue. With the compilation of the analysis of results, a series of guidelines is developed with recommendations for the planning of a well, actions to be taken into account during drilling and those to maintain well stability.